Caractérisation et Evaluation des aptitudes technologiques des Lactocoques isolés d’une crème fraiche crue destinée à la transformation industrielle. - MOKAREM, Fatima (My University, 2016)
The aim of our work is to isolate and identify lactic acid bacteria from produce frais be derived from milk cream fraichegrow. Thirty six strains were isolated from one sample of cream fraiche grow take it SARL HODNA MILK M’SILA. The identification was carried out by performing many microbiological and biochimical tests that led to the identification of the following in two genera :LactococcusandEnterococcus. Analysis of the results showed a dominance of Lactococcusamong isolates purified.as well as analysis of the results showed that strains of Lactococcusisolates have got good aptityd technological. In the end, we have try use this isolates of Lactococcus in to making the cream mature.
Keywords: bactéries lactiques; la crème fraiche crue; l’identification; Lactococcus; Enterococcus; aptitudes technologiques; crème maturée.; البكتیریا اللبنیة; القشدة الطازجة; تمییز; لاكتكوكوز; اونتغكوكوز; القشدة الیانعة; كفاءة تكنولوجیة; lactic acid bacteria; cream fraiche grow; The identification; aptityd technological; cream mature.